Czas historyczny i doświadczenie: Strategia opisu przeszłości w epopei Czerwone Koło Aleksandra Sołżenicyna .......... 535 - Sidor, Monika (Czas w kulturze rosyjskiej, 2019)
HISTORICAL TIME AND EXPERIENCE. STRATEGY OF DESCRIBING THE PAST IN THE RED WHEEL BY ALEKSANDR SOLZHENITSYNAleksandr Solzhenitsyn claimed that The Red Wheel depicts the genesis of the Russian Revolution and combines the elements of historiography and literature. The goal of this epic was to overcome the limitations which a history researcher meets. The writer used many means and techniques which were unusual for a literary work, such as documents, diplomatic correspondence, or so-called “screens”. The author of the paper puts forward the thesis that the category of experience played a main role in the Solzhenitsyn’s work. The article presents different aspects of this concept in the works of The Red Wheel cycle.